2014
DOI: 10.17221/50/2013-swr
|View full text |Cite
|
Sign up to set email alerts
|

A model experiment: competitive sorption of Cd, Cu, Pb and Zn by three different soils

Abstract: Zemanová V., Trakal L., Ochecová P., Száková J., Pavlíková D. (2014) The results of the model experiment confirmed that the sorption from single-metal solution was more effective than sorption under multi-metal conditions, due to competitive effects. In all tested soils sorption of Cd, Cu and Zn decreased with the rate of other competitive metals; the Pb sorption was not affected by other competitive metals in solutions. Moreover, during multi-metal sorption, Zn was significantly desorbed in Cambisol. In gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Regeneration studies indicated that HCl provided the highest desorption capacity but with most material damage. Zemanova et al 30 carried out investigation on competitive sorption of Cd, Cu, Pb and Zn 30 . For adsorption experiments he used three types of soil.…”
Section: Multicomponent and Competitive Sorption Of Heavy Metalsmentioning
confidence: 99%
“…Regeneration studies indicated that HCl provided the highest desorption capacity but with most material damage. Zemanova et al 30 carried out investigation on competitive sorption of Cd, Cu, Pb and Zn 30 . For adsorption experiments he used three types of soil.…”
Section: Multicomponent and Competitive Sorption Of Heavy Metalsmentioning
confidence: 99%
“…This property is associated with the high reactivity of fine particles that contain minerals of clay, iron/manganese/aluminum oxide and humic acid [61]. The sorption strength of TEs is characteristic of soil type [62], since the processes of sorption and bioavailability of TEs are influenced by soil mineral composition, iron/manganese/aluminum oxide and hydroxides, silicates, phosphates, carbonates, soil and humic acids, and organic colloids [44,61,63]. Depending on the mentioned physicochemical properties and processes in the soil, the mobility of TEs can vary greatly in different soil types [15,64].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the effect of soil-applied biochars from different stock biomasses on rhizosphere microbiota, durum wheat plant performance, and soil properties in low metal-contaminated soil has not been investigated. This study focused on soil originating from the vicinity of a mining/smelting district (Přibram, Czechia), 12 km distant from the heavily contaminated soil, and followed up several previous studies dealing with bulk metal contamination in this area (Zemanová et al, 2014;Jačka et al, 2018). In the present study, two different biochars (i.e., wood and wheat straw), both manufactured at a high pyrolysis temperature (700 • C), and two durum wheat varieties exhibiting different behavior and traits, thus reflecting the level of influence of the plant genotype to the biochar treatment, were used with the aim of assessing the effect of biochar type and/or durum genotype on the diversity and composition of microbiota associated with rhizosphere soil, soil properties, and plant growth.…”
Section: Introductionmentioning
confidence: 99%